y = (x2 – 2x + 1) y = (x – 1)(x – 1) Prove that the following functions are equivalent through algebraic and numerical proof

Question

y = (x2 – 2x + 1)
y = (x – 1)(x – 1)
Prove that the following functions are equivalent through algebraic and numerical proof

in progress 0
Thu Nguyệt 5 months 2021-09-05T00:53:41+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-09-05T00:55:08+00:00

    y = (x^2 – 2x + 1)

    y = (x – 1)(x – 1)

    Algebraic Proof

    FOIL y = (x – 1)(x – 1)

    y = (x – 1) (x -1 ) = x^2 -2x + 1

    Done.

    Numeric Proof

    Let x = 1

    y = x^2 – 2x + 1

    y = (1)^2 – 2(1) + 1

    y = 1 – 2 + 1

    y = 2 + 2

    y = 0

    Let x be 1 again.

    y = (x – 1)(x – 1)

    y = (1 – 1)(1 – 1)

    y = 0

    There you have it. Both equations are the same.

    0
    2021-09-05T00:55:20+00:00

    Answer:

    see below

    Step-by-step explanation:

    y = (x² – 2x + 1)

    y = (x – 1)(x – 1)

    First, recognize that the first equation is fully simplified/expanded already.

    Now, we should solve for the second equation.

    FOIL the expressions: first–outer–inner–last

    (x – 1)(x – 1)

    F: x²

    O: -x

    I: -x

    L: 1

    Combine these terms.

    x² – x – x + 1

    x² – 2x + 1

    Notice that this equation is identical to our first equation. Therefore, the functions are equivalent.

    Hope this helps!

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )